Representasi Feminisme Tokoh Utama Dalam Film “She-Hulk Season 1 : Episode 1” - Mukhammad Shobri Kamil (Jurnal Ilmu Komunikasi, 2022)
Currently, the campaign for the feminist movement has reached its third wave, namely the post-feminism wave. The movement was born because young women in the 1980s felt that the feminist movement was unsatisfactory and boring. Supported by the development of information technology, it is possible for post-feminism movement campaigns to be carried out through discourse in the form of writing, pictures, films, and other electronic forms. One way is to use film to convey the idea of feminism to the general public. Nowadays, many film studios have released films with female main characters as a form of concern for upholding gender equality between men and women. One of these films is the film series "She-Hulk: Attorney at Law" season 1 episode 1. The purpose of this research is to find out how the representation of feminism of the main character in the film series "She-Hulk: Attorney at Law" season 1 episode 1. This research uses descriptive-interpretative qualitative methods as well as Roland Barthes' semiotic theory to analyze and find out the signs that represent the main character's feminism in the related film. The results of this study indicate that the main character “Jennifer Walters” in the film series "She-Hulk: Attorney at Law" season 1 episode 1, represents liberal and radical feminism. In addition, Roland Barthes' semiotic analysis in this study found a myth that related to the related film. The myth is that if women want to be seen as equal to men, they must have super powers to equal them. In fact, in real life you don't have to have super powers to be equal to men.